Leadership and Health Security During the Covid-19 Pandemic: Case Analysis in Indonesia - Anggi Koenjaini Putri; Gideon Candra Agape; Renitha Dwi Hapsari; Firsty Chintya Laksmi Perbawani; Maria Indira Aryani (Nusantara Science and Technology Proceedings, 2022)
This research examines the correlation between leadership politics and health security in handling the Covid-19 pandemic in Indonesia (Surabaya City area). This research focuses on the Omicron cases in Indonesia, from February 1, 2022, to April 4, 2022. This study examines the public response to policies issued by the Government to tackle the spread of the Covid-19 virus, precisely vaccination policies and the implementation of activity restrictions. This study uses a qualitative-descriptive approach with a structured questionnaire survey observations and interviews to measure public responses to the policy created by leaders. Theoretical and empirical evidence shows that public trust in Government is critical to general compliance with social policies. The survey results that have been carried out show solid public belief in the Government when controlling COVID-19 during the Omicron, which is indicated by the public's interest in adopting proportional health behaviors following vaccination policies and restrictions on social activities. Interview responses from health medical personnel and political elites, the House of Representatives as policy supervisors, showed that the surge of patients during the Omicron wave could handle because prevention was more prepared to prevent the risk of death. In addition, the public accepts government policies that are more organized in responding to the Covid-19 pandemic during the Omicron by conveying information. So this perception with a higher level of trust in the Government. The Government of Indonesia's leadership practices appears to be on the right track regarding public health security measures during the Omicron wave. Therefore, the expression of public trust is not something instant. It is influenced by public confidence in the policy presented and processed by the Government so that faith in obeying the rules can control people's behavior.